Fitness-related selection on floral traits in the distylous plant Primula poissonii (Primulaceae). (7th June 2016) - Li, Hai-Dong; Zhao, Yan-Hui; Ren, Zong-Xin; Wu, Zhi-Kun; Wolfe, Lorne M.; Bernhardt, Peter; Wang, Hong
Abstract: Aims: Reproductive fitness of different floral phenotypes varies within and/or among populations. These variations are important to understand the process of natural selection and the evolution of floral traits. In this study, we focused on a distylous, self-incompatible species, Primula poissonii, to investigate fitness-related selection on floral traits. Our aim was to determine how traits vary as targets of natural selection and whether morph-specific selection occurs. Methods: This study was conducted at two sites (Yushuizhai at 2700 m and Haligu at 3200 m) in the Lijiang Alpine Botanical Garden, northwestern Yunnan, southwestern China. Insects visiting flowers of P. poissonii were observed, captured and identified. Randomly selected plants of long- and short-styled morphs were labeled. Five floral/inflorescence traits were measured including floral display, corolla width (CW), floral tube length (FTL), tube opening width (TOW) and floral scape height. Fruit and seed set were recorded. The total number of seeds per individual plant (plant fitness) and seed production per capsule (flower fitness) were calculated. Multiple regression analyses were used to quantify selection gradients. Important Findings: The frequencies of the two morphs did not deviate from the expected 1:1 ratio at both sites. Except for FTL, the four other traits did not differ significantly between the long- and short-styled morphs. Floral scape height, floral display and FTL differed between two sites. The selection regimes differed between two morphs and between two sites. At the Yushuizhai site, linear selection for shorter floral tubes was stronger in the short-styled morph. However, nonlinear selection on the floral display was stronger in the long-styled morph than selection on the short-styled morph. At the Haligu site, linear selection for a smaller corolla was stronger in the long-styled morph. A morph-specific nonlinear selection on CW and floral display was also detected. Morph-specific selections were detected through the estimation of flower fitness only in Haligu population. In this site, morph-specific linear selection was also detected for CW and floral display. Morph-specific nonlinear selection on traits was detected only in CW. We found that butterflies and sphingid moths dominated at Yushuizhai, while long-tongued bees dominated at Haligu. The difference in pollinator fauna suggested that selection on floral tubes may be due to differences in pollinator assemblages. Overall, variation of floral and/or inflorescence traits in P. poissonii was probably driven by pollinator selection. Selection regime differences between two morphs, in part, due the inter-morph divergences of sexual functions in distylous plant.